Microstructural design by severe warm-rolling for tuning mechanical properties of AlCoCrFeNi2.1 eutectic high entropy alloy. (November 2019) - Reddy, S.R.; Sunkari, U.; Lozinko, A.; Saha, R.; Guo, S.; Bhattacharjee, P.P.
Abstract: The influence of severe warm-rolling and subsequent annealing on the microstructure and mechanical properties in an AlCoCrFeNi2.1 high entropy alloy consisting of a lamellar arrangement of ordered L12 and B2 phases was studied. For this purpose, the as-cast EHEA was severely warm-rolled up to 90% reduction in thickness at selected temperatures of 400 °C, 600 °C, and 750 °C. The severely warm-rolled EHEAs were further annealed at temperatures ranging from 800 °C to 1200 °C for 1 h. Warm-rolling resulted in a unique disordering behavior of the L12 depending on the temperature of warm-rolling. However, the B2 phase maintained the ordered structure irrespective of the warm-rolling temperature. The EHEA warm-rolled at 400 °C and 600 °C showed a predominantly lamellar microstructure, while the EHEA warm-rolled at 750 °C showed a novel heterogeneous microstructure featured by a mixture of lamellar and non-lamellar regions. Annealing of the 90% warm-rolled materials resulted in the formation of predominantly duplex microstructures consisting of disordered FCC and B2 phases. The EHEA warm-rolled at 400 °C and 600 °C showed high strength but rather limited ductility, which could be improved upon annealing. Remarkably, the EHEA warm-rolled at 750 °C showed the most outstanding properties featured by exceptional strength-ductility combination owing to the novel heterogeneous microstructure. Annealing of the heterogeneous EHEA resulted in the deterioration of the strength-ductility balance owing to the annihilation of the heterogeneous microstructure, being replaced by a microduplex structure. Highlights: The AlCoCrFeNi2.1 was severely warm-rolled at different temperatures and annealed. Unique disordering behavior was observed depending on the rolling temperature. Novel heterogeneous structure by warm-rolling at 750 °C showed outstanding properties. Elimination of heterogeneous structure due to annealing resulted in inferior properties.